Modeling, computation and optimization - Neogy, S. K.; Das, A. K. (Arup Kumar); Bapat, R. B. (Statistical science and interdisciplinary research, 2009)
This volume provides recent developments and a state-of-the-art review in various areas of mathematical modeling, computation and optimization. It contains theory, computation as well as the applications of several mathematical models to problems in statistics, games, optimization and economics for decision making. It focuses on exciting areas like models for wireless networks, models of Nash networks, dynamic models of advertising, application of reliability models in economics, support vector machines, optimization, complementarity modeling and games.